2016
DOI: 10.1002/jlcr.3389
|View full text |Cite
|
Sign up to set email alerts
|

Identification andin vivoevaluation of a fluorine-18 rolipram analogue, [18F]MNI-617, as a radioligand for PDE4 imaging in mammalian brain

Abstract: Phosphodiesterase (PDE) 4 is the most prevalent PDE in the central nervous system (CNS) and catalyzes hydrolysis of intracellular cAMP, a secondary messenger. By therapeutic inhibition of PDE4, intracellular cAMP levels can be stabilized, and the symptoms of psychiatric and neurodegenerative disorders including depression, memory loss and Parkinson's disease can be ameliorated. Radiotracers targeting PDE4 can be used to study PDE4 density and function, and evaluate new PDE4 therapeutics, in vivo in a non-invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Very recently, Thomae et al [82,83] reported on the development of structurally modified derivatives of ( R )- 6 with the aim to generate 18 F- and 123 I-labeled PDE4 radioligands for PET or SPECT application, respectively. In general, low tolerance of PDE4 for structural changes in ( R )- 6 has been stated as well as a significant decrease in PDE4 affinity for the iodo derivatives that consequently have been suggested to be not suitable as SPECT radioligands.…”
Section: Pde4 Radioligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Thomae et al [82,83] reported on the development of structurally modified derivatives of ( R )- 6 with the aim to generate 18 F- and 123 I-labeled PDE4 radioligands for PET or SPECT application, respectively. In general, low tolerance of PDE4 for structural changes in ( R )- 6 has been stated as well as a significant decrease in PDE4 affinity for the iodo derivatives that consequently have been suggested to be not suitable as SPECT radioligands.…”
Section: Pde4 Radioligandsmentioning
confidence: 99%
“…In general, low tolerance of PDE4 for structural changes in ( R )- 6 has been stated as well as a significant decrease in PDE4 affinity for the iodo derivatives that consequently have been suggested to be not suitable as SPECT radioligands. Out of this series, the fluorinated analogue 7 (MNI-617, Figure 2) has been described as the most promising compound with a five-fold increased PDE4 affinity over ( R )- 6 ( K D = 0.26 nM vs. 1.6 nM) and thus has been selected for 18 F-labeling [82,83].…”
Section: Pde4 Radioligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiochemical yields are comparable and range from 60 to 80% for the final alkylation step. 37,52,53 Analogous to the O-alkylation, aromatic S-alkylation of guanidine derivative 18 has been performed (Scheme 10). The reaction was carried out in MeCN at 110 1C for 15 minutes using cesium carbonate as base.…”
Section: [ 18 F]fluoromethyl Halides and Sulfonatesmentioning
confidence: 99%
“…Reactions with [ 18 F]fluoromethyl tosylate. Scheme 9 O-Alkylated tracers with [ 18 F]fluoromethyl tosylate 37,52,53. Scheme 10 Synthesis of a S-fluoroalkyl guanidine derivative 54.…”
mentioning
confidence: 99%